The relationship between sugary-sweetened beverages (SSB) intake, anthropometric indices and fasting blood glucose (FBG) level among male and female students from Universiti Tunku Abdul Rahman (UTAR) Kampar - Yeo, Yee Teng (2023)
Currently, there is a high prevalence of sugar-sweetened beverage (SSB) consumption among young adults especially teenager students and its added sugar contents would contribute to various chronic diseases especially diabetes. Therefore, it is very crucial to understand the factors associated with SSB intake in relation with anthropometric indices and fasting blood glucose (FBG) levels. The objective of this study was to determine the relationship between SSB intake, anthropometric indices and FBG among male and female students from Universiti Tunku Abdul Rahman (UTAR) Kampar. A cross-sectional study was conducted and 200 eligible UTAR Kampar students were recruited using a quota sampling method. Respondents were needed to complete survey comprised of sociodemographic data, frequency and amount of beverages intake through validated Beverage Intake Questionnaire (BEVQ-15), anthropometric measurement and fasting blood glucose test. Kruskal Wallis test and Mann-Whitney test were used to examine the comparison while spearman correlation determined the relationship between SSB, anthropometrics with FBG. This study had revealed that UTAR students had a low SSB intake <1 time per day, normal anthropometric measurements and FBG levels. Male consumed a significantly higher amount of SSB thane female students (p=0.001). A significant difference of BMI, waist circumference, body fat percentage and FBG. Male students had a significantly higher BMI, WC and FBG whereas only body fat percentage was higher in female students. No correlation between BMI and body fat percentage with FBG. A positive correlation between SSB and WC with FBG (r=0.189, p=0.007) and (r=0.151, p=0.033), respectively. Lastly, there was a significant difference (p=0.014) of FBG between different BMI categories. To conclude, the SSB intake of UTAR students was not concerning. However, there is still few students having the risk of prediabetes especially among those who were overweight. Therefore, further educational interventions are needed to be implemented to prevent the onset of diabetes